Perspectives from research and practice: A survey on external load monitoring and bone in sport - Scott, Reece; James, Ruth; Barnett, Cleveland T.; Sale, Craig; Varley, Ian (Frontiers in Sports and Active Living, 2023)
There is limited information regarding the association between external load and estimated bone load in sport, which may be important due to the influence exercise may have on bone accrual and injury risk. The aim of this study was to identify external load measuring tools used by support staff to estimate bone load and assess if the methodologies were supported in research. A survey was comprised of 19 multiple choice questions and an option to elaborate on if/how they monitor external load and if/how they used them to estimate bone load. Participants took part if their role involved working as support staff in applied sport. Support staff (n=71) were recruited worldwide with the majority (85%) working with professional elite athletes. 92% of support staff monitored external load in their organisation, but only 28% used it to estimate bone load. The most common methods used to estimate bone load were IMUs and motion capture. External load is commonly monitored in sport, but it is not often used to estimate bone load. There is no consistent method that is used to estimate bone load by support staff in an applied setting.